Treatment-Associated Anxiety among Pregnant Women and their Partners: What is the Influence of Sex, Parity, Age and Education? - Kannenberg, K.; Weichert, J.; Rody, A.; Banz-Jansen, C. (Geburtshilfe und Frauenheilkunde, 2016)
Background: Anxiety during pregnancy can influence outcomes negatively. The aim of this study was to assess the fears of expectant parents in the setting of antenatal and obstetric care according to their sex, age, parity and education. Methods: 259 pregnant women and 183 partners, who had presented for antenatal investigation, routine antenatal care or for delivery in the UKSH womenʼs hospital, Lübeck campus, completed a self-assessment questionnaire of fears and the German version of the STAI (Laux et al.). ANOVA and t-tests were used for significance testing. Results: Pregnant women had higher levels of trait anxiety and state anxiety than their partners. Level of education had a significant, inverse effect on trait anxiety. Age had no influence. Fears for the childʼs health ranked highest among pregnancy-specific fears. Expectant fathers had the same level of anxiety for the birth irrespective of parity; for women fear of the birth decreased with increasing parity. Anxiety only increased significantly for expectant fathers from the 20th week of gestation onwards. Conclusions: Pregnant women and their partners have different levels of anxiety dependant on their age, education, parity and the stage of pregnancy. These findings could contribute towards improving support of couples during pregnancy. The fears of expectant fathers require particular attention.
Keywords: pregnancy; pregnancy-related anxiety; expectant couples